LINKING CARBON DISCLOSURE AND CARBON PERFORMANCE TO FIRM VALUE: AN INTEGRATED ENVIRONMENTAL VALUE CREATION MODEL - V. Ananta Wikrama Tungga Dewi; Indi Aidilia (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study investigates the impact of financial flexibility, CSR disclosure, carbon emission reporting, and carbon performance on the valuation of Indonesian energy firms (2019-2023), moderated by corporate governance. To address the research objectives, a quantitative framework was utilized through panel data regression analysis with STATA 15. This study comprised 42 energy sector companies, selected via purposive sampling. The findings elucidate that financial slack has an influential positive effect on firm value, while CSRD has no direct effect but becomes influential when moderated by corporate governance. CED has an influential positive effect on firm value, while CP demonstrates no measurable impact. These findings confirm that transparency of social and environmental information is more valued by the market than actual environmental performance in creating sustainable value.